INCREASING STUDENTS’ INTERCULTURAL COMMUNICATION COMPETENCE BY UTILIZING BLENDED LEARNING MODEL - Sugeng Susilo Adi (Universitas Brawijaya, 2017)
This article is a summary of a qualitative observation to the students of English Education Program, Brawijaya University, Indonesia. It tries to describe the students’ learning experiences, perception, and expectation about issues related to the contents, that is intercultural communication; and learning methodology, particularly blended learning. As foreign language students, the subjects of this observation need to achieve not only language competence but also intercultural communication competence because when they communicate with people coming from different cultural backgrounds they should understand their communication styles as a part of their culture. Meanwhile, the advancement of information technology and communication (ITC) affects the teaching and learning strategy where blended learning has been very popular applied in some universities. This research employs three parallel classes in Cross Cultural Understanding course. Qualitative observation, document analysis, and online interviews were conducted to gain students pedagogical interaction, learning experiences, and expectation about both intercultural communication competences and blended learning strategy. The study reveals that students have new perspectives about the role of culture in communication especially the use of language as a medium of communication. Students also realize that living in a multicultural society needs an intercultural awareness to avoid misunderstanding caused by prejudice and overgeneralization toward people coming from different cultural background. Abouut the blended learning strategy applied in the course, students find it is interesting. The strategy motivates their learning activities because the media used is similar to social media that have been very familiar with their daily life. Keywords: intercultural, communication, competence, blended learning, awareness, misunderstanding